Decreasing Symptoms of Risk of Violent Behavior in Schizophrenia Patients Through Group Activity Therapy - Jek Amidos Pardede; Bijaksana Laia (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The risk of violent behavior is a symptom of schizophrenia patients that can be controlled through Perception Stimulation Group Activity therapy. Therapy Activity Group Perception Stimulation is an effort to train clients to perceive the stimulus provided or stimulus that has ever been experienced. The purpose of this study was to determine the effect of Perception Stimulation Group Activity Therapy on changes in risk symptoms of violent behavior in schizophrenic patients. This study uses a quasi-experimental pre-post test method. The population in this study amounted to 168 people with a total sample of 17 people. The sampling technique was purposive sampling. The research instrument used was a questionnaire and observation sheet. The results of this study were analyzed by univariate analysis and bivariate analysis by Paired T-Test. The results showed there was an influence of Perception Stimulation Group Activity Therapy on Changes in Risk Symptoms of Violent Behavior before and after Group Activity Therapy with P-value = 0,000 <p = 0.05. Researchers concluded that group activity therapy had a significant effect on reducing the risk symptoms of violent behavior in Prof. Dr. Muhammad Ildrem Provsu mental hospital Medan City.